In vitro establishment of Vaccinium consanguineum, a native blueberry from Costa Rica - Jiménez-Bonilla, Vilma (2016)
In Costa Rica, blueberry is one of the wild species whose domestication has aroused great interest, since it is horticulturally promising. For this reason it was included as a line of research in the area of non-traditional fruit crops in the Fruit Growing National Program (Eng. Alberto Montero, national program manager of the non-traditional fruits in the Ministry of Agriculture and Livestock, November 2014, San Jose, Costa Rica, personal communication). The objective of this research was to develop a protocol for in vitro establishment of this species, as part of the blueberry project: an option for the diversification of agriculture in the Highlands of the country, in order to count with aseptic material that allows to continue with the development of the following stages of micropropagation process. For the in vitro establishment, micro cuttings with 2 and 3 knots were taken directly from the field, washed with detergent and water for 30 minutes, then were disinfected with several solutions such as sodium and calcium hypochlorite and Mercury chloride (HgCl2), in various concentrations. The solution that allowed the highest percentages of micro cuttings established aseptically was HgCl2 0.2% for 5 minutes. The medium used was a WPM with 1 g/l of activated charcoal. Micro cuttings established aseptically will be utilized to assess the effect of multiple regulators of growth in the sprouting of buds.